Prospective observational study of the challenges in diagnosing common neonatal conditions in Nigeria and Kenya - Melissa Gladstone; Janneke van de Wijgert; Nicholas D Embleton; Kevin Mortimer; Beatrice N Ezenwa; Isa Abdulkadir; Olusegun Akinyinka; Chinyere Ezeaka; Walter Otieno; Graham Devereux; Ismaela Abubakar; Iretiola B Fajolu; et al. (BMJ Open)
Objectives Accurate and timely diagnosis of common neonatal conditions is crucial for reducing neonatal deaths. In low/middle-income countries with limited resources, there is sparse information on how neonatal diagnoses are made. The aim of this study was to describe the diagnostic criteria used for common conditions in neonatal units (NNUs) in Nigeria and Kenya.Design Prospective observational study. Standard case report forms for suspected sepsis, respiratory disorders, birth asphyxia and abdominal conditions were co-developed by the Neonatal Nutrition Network (https://www.lstmed.ac.uk/nnu) collaborators. Clinicians completed forms for all admissions to their NNUs. Key data were displayed using heatmaps.Setting Five NNUs in Nigeria and two in Kenya comprising the Neonatal Nutrition Network.Participants 2851 neonates, which included all neonates admitted to the seven NNUs over a 6-month period.Results 1230 (43.1%) neonates had suspected sepsis, 874 (30.6%) respiratory conditions, 587 (20.6%) birth asphyxia and 71 (2.5%) abdominal conditions. For all conditions and across all NNUs, clinical criteria were used consistently with sparse use of laboratory and radiological criteria.Conclusion Our findings highlight the reliance on clinical criteria and extremely limited use of diagnostic technologies for common conditions in NNUs in sub-Saharan Africa. This has implications for the management of neonatal conditions which often have overlapping clinical features. Strategies for implementation of diagnostic pathways and investment in affordable and sustainable diagnostics are needed to improve care for these vulnerable infants.